Is there a link between no fault found and airworthiness? - Lacey, Laura (Cranfield University, 2023)
The no fault found phenomenon negatively impacts the aviation industry and an aircraft’s airworthiness. Airworthiness and no fault found must be appreciated during the design, maintenance and subsequent operation. This research aimed to establish if a link between no fault found and airworthiness exists and to garner the aircrew's perception of any possible link. Semi-structured interviews and a questionnaire were conducted to generate primary data. Pilots and aircraft accident investigator interviews were conducted to establish a foundation of knowledge, experience and perspectives on no fault found and airworthiness to support the questionnaire. The questionnaire established predominately RAF aircrew views on the impact of no fault found on airworthiness, the key aircraft systems affected, communication methods and associated training completed. Secondary data from an aviation company’s maintenance records were analysed for no fault found frequencies. The research analysis includes systems engineering, Bowtie, Functional Resonance Analysis Method and fuzzy logic inference. The RAF aircrew canvassed perceives no fault found to negatively impact airworthiness causing missions to be cancelled, curtailed or replanned. Trust between RAF aircrew and engineers is diminished. This impacts the analysis and recording of no fault found and airworthiness. Training the aircrew and engineers on how to conduct the post-sortie engineering debrief, in a dedicated location, whilst using a dedicated proforma that focuses on no fault found and airworthiness, and reviewing the aircraft’s no fault found history will decrease the occurrences of the phenomenon. An iterative relationship between Bowtie and Functional Resonance Analysis Method established the key aspects that impact the link between no fault found and airworthiness. Based on mission success, the fuzzy logic inference of the aircrew and RAF engineers’ linguistic variables, (negligible to severe), that described the aircraft’s airworthiness level as a consequence of repeated no found faults, were combined to create 3-dimensional surface plots to represent the aircraft’s overall airworthiness level. These combined confirmed that airworthiness is not binary. These original 3-dimensional surface plots indicate the no fault found/airworthiness relationship varies over longer periods but is most pronounced in shorter periods with more no fault found occurrences. This indicates that the current methods for analysing and assessing the impact of no fault found on airworthiness require redefining and this research suggests that no fault found /Airworthiness working groups with key stakeholders are a means to achieve this. As the questionnaire participants were mainly RAF aircrew the external validity for them has been established. However, the wider validity of this research with other aviation organizations cannot be stated categorically unless further research is conducted.
Place, Simon - Associate Supervisor
Keywords: Aircrew; Bowtie; engineer; fault not found; FRAM; Functional Resonance Analysis Method; fuzzy logic; inference; NFF; post-sortie engineering debrief; surface plot; trust